'I'm like you, you're like me, we make a great brand community!' Similarity and children's brand community participation. (January 2020) - Hook, Margurite; Baxter, Stacey; Kulczynski, Alicia
Abstract: Moving beyond a common brand interest, homophily is employed to understand the impact of characteristic similarity between child members of a brand community on attitudes toward the brand community and community participation desire. Three experimental studies were undertaken, assessing member similarity, respect, and member deviance with relation to brand community attitudes and participation desire. Results suggest greater similarity enhances children's attitudes toward the community and participation desire, explained by an increased respect towards the community. When a community member is deviant (disloyal), respect, and subsequently attitudes and participation desire, decline. By introducing homophily to child-oriented brand communities; this research contributes to the sparse literature, with results highlighting marketers should emphasize member similarity when promoting brand communities aimed at children.